LAS ESPECIES CHILENAS DEL GÉNERO COLLETES (HYMENOPTERA:COLLETIDAE): CLAVE DE ESPECIES - Toro, Haroldo (Acta Entomológica Chilena, 2022)
The chilean species of Calieres are considered in this paper; the following species are keyed out: C. alocochila Moure, 1956; C. araucariae Friese,1910; C.atacamensis Janvier.1955; C. atripes Smith,1854; C.bicolor Smith, 1879; C. chusmiza Rojas y Toro, 1993; C.cognatus Spinola, 1851; C.cyanescens Spinola, 1851; C. flaminii Moure,1956; C.fulvipes Spinola, 1851; C.gilvus Vachal,1909; C. guanta Rojas y Toro, 1993; C. longiceps Friese,1910; C.lucens Vachal, 1909; C. mastochila Moure, 1956; C. musculus Friese,1910; C.neoqueenensis Friese,1910; C. nigritulus Friese,1910; C. patagonicus Schroltky, 1907; C.quelu Rojas y Toro, 1993; C. rutilans Vachal, 1909; C. seminitidus Spinola, 1851; C.vicugnensis Rojas y Toro, 1993. The geographic dislribution of ihe species and the association with flowers are given.